The Existence of Modern Mini Markets amidst Traditional Retail Market - Andi Ayu Frihatni (Publisher Cv. Inara, 2020)
This research aims at discussing the existence of modern mini market consisting amidst traditional retail market. I t was conducted at Parepare, South Sulawesi, Indonesia. Modern mini market in this research consisted of the Alfamart, Indomaret, and Alfamidi. The data analysis used in this study used a quantitative approach. The data analysis techniques in this study use descriptive statistics and simple regression as well as paired t-test. The result of this research found that the existence of modern mini market has no effects on the going concern of traditional retail market.